2009
DOI: 10.1149/1.3202668
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning and Damage Performance of Single Wafer Cleaning Tools using Physical Removal Forces

Abstract: We evaluated the trade off between damage generation and particle removal of single wafer aerosol spray and megasonic cleaning tools. This was done by the calculation of the local particle removal rates of 30 nm silica and the local damage fluxes of ~ 20 nm wide amorphous-Si lines.Cleaning and damage nonuniformities observed for aerosol cleaning were due to different exposure times to the spray nozzle. The non-uniformities for megasonic cleaning were due to different exposure times to the rod as well as to non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…If f R is assumed to be constant over time, it can be shown that PRE is an exponential decay function of time [3]. In Figure 3 we give the boxplots of the averaged removal rates f R as a function of the radial positions R. It appears that f R increases almost linearly with the radial distance from the wafer center and then reaches a plateau from approximately R=40 mm.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…If f R is assumed to be constant over time, it can be shown that PRE is an exponential decay function of time [3]. In Figure 3 we give the boxplots of the averaged removal rates f R as a function of the radial positions R. It appears that f R increases almost linearly with the radial distance from the wafer center and then reaches a plateau from approximately R=40 mm.…”
Section: Resultsmentioning
confidence: 97%
“…was determined by haze measurements using a KLA SP2 tool with a spatial resolution of 0.6 mm, where σ o and σ(t) are used to denote the initial and instantaneous particle surface concentrations respectively [1,3].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nanopatterns on the 300 mm silicon substrates are periodic silicon lines with 30 nm linewidth and 500 µm spacing. The silicon lines have an high K-metal gate interface (HfO 2 /Al 2 O 3 /TiN) and are 100 nm high and 1 mm long (9)(10)(11). The wafers were measured using a brightfield inspection tool (KLA2835) before and after controlled contamination and after clean.…”
Section: Experimental Methodsmentioning
confidence: 99%